Current research trends and hotspots of boron neutron capture therapy: a bibliometric and visualization analysis - Cong, Yuyang; Abulimiti, Muyasha; Matsumoto, Yoshitaka; Jin, Jing (Frontiers in Oncology, 2024)
PurposeThis study aimed to describe the trends, current hotspots, and future directions in boron neutron capture therapy (BNCT) through a bibliometric analysis.MethodsArticles related to BNCT published before 2023-12-31 were retrieved from the Web of Science Core Collection database. VOSviewer, R, and CiteSpace were used for bibliometric analysis and visualization.ResultsA total of 3347 related publications from 1975 to 2023 were retrieved. Since a burst of published documents in 1992, the past three decades have witnessed continuous investigations into BNCT-related studies. Japan was the most productive country (794, 23.72%), followed by the USA (792, 23.66%), while the latter had the most citations. Kyoto University was the most influential institution. Ono K was the most prolific author, and Applied Radiation and Isotopes was the most popular journal. Ono K was the author that had the most total citations, followed by Barth RF. “Carborane”, “boronophenylalanine”, “glioblastoma”, “sodium borocaptate”, “cancer” and “drug delivery” were the most frequent keywords. The article “Dendrimers and dendritic polymers in drug delivery” had the most citations, whereas “Boron delivery agents for neutron capture therapy of cancer” had the highest outbreak value.ConclusionOver the past three decades, research on BNCT has expanded significantly, with the development of novel boron carriers with improved medicinal characteristics being the most extensively investigated area. Future research will likely focus on the validation and modification of current BNCT treatment modalities using conventional boron agents in brain tumors, accelerator-based neutron sources and the application of BNCT in more clinical scenarios.